The potential protective role of vitamin D and calcium supplements in reducing cardiovascular disease risk among elderly patients with osteopenia - Ramada R. Khasawneh (6837734) (2024)
Background Cardiovascular disease and low bone mineral density are major health problems in the elderly. These two conditions are considered independent of each other and age-related diseases. The aim of this study is to investigate the association between low bone mineral density (BMD) and cardiovascular disease (CVD) incidents, and the effect of vitamin D and calcium supplement on the incidence of CVD in patients with low BMD. Methods A total of 1047 patients (597 females/450 males) with the age of 65 years and more were diagnosed with osteopenia for 13 years or more. The study also included 220 patients (107 females/113 males) with osteopenia who already took calcium and vitamin D continually since their diagnosis. BMD was measured by dual-energy X-ray absorptiometry. The incidence of any cardiovascular diseases in the study patients and the presence of corresponding risk factors were collected and analyzed. Results In both elderly Arab females and males, there was an association between total hip and femoral neck BMD and the possibility to have CVD. On the other hand, the results showed that patients who use calcium and vitamin D supplements showed a significant reduction in the incidence of CVD comparing to the non-treated patients. Conclusion Low total hip and femoral neck BMD were associated with a higher chance to have CVD incidents in both elderly Arab males and females; moreover, calcium and vitamin D supplements have a possible protective role in reducing cardiovascular disease in elderly patients with osteopenia. Other Information Published in: Irish Journal of Medical Science (1971 -) License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11845-024-03709-2